The Impact of Reinforcement Towards Students’ Confidence and Motivation in Learning English - Merilyn Ivoni Todang; Nurdi Noni; Muhammad Basri Jafar (International Journal of Language, Education, and Literature, 2025)
This research objectives are outlined: 1) to describe the students’ perception towards reinforcement. 2) to describe how reinforcement is implemented 3) to elaborate the types of reinforcement that the teacher regularly uses in teaching and learning process. A qualitative method with a case study design was employed. The subjects of the research were an English teacher and students from fifth grade. The data were analyzed using thematic analysis. The findings of the research showed that the impact of reinforcement on the students was notably positive. Students’ perceptions of reinforcement within the teaching and learning process have shown influence to students’ engagement, motivation, and overall attitude towards learning. Many students expressed that receiving reinforcement from their teacher made them feel happy, great, and proud. Most students reported feelings of sadness, fear, and a sense of failure when subjected to punishment. Based on the observation, the types of reinforcement used by the teacher in the teaching and learning process can be classified into several categories: verbal reinforcement, nonverbal reinforcement, vicarious reinforcement, delayed reinforcement, and qualified reinforcement. Keywords: Reinforcement, Students’ Perception, Students’ Confidence, Students’ Motivation